Comprehensive study on antioxidant activities of lutien and beta-carotene and their properties in cellular level - Lestari, Widya; Jaswir, Irwandi (2016)
Radical scavenging and singlet oxygen quenching activities of the conjugated polyene structure owned by carotenoids were believed to have beneficial effects on human health. However, under certain conditions, for instance high concentration of carotenoids and high oxygen tension have led to a potential prooxidant action of carotenoids in vitro. This study was aimed to evaluate antioxidant activities of high concentration of major dietary carotenoids in human hepatoma HepG2 cells. The cells that accumulated carotenoids and α-tocopherol at the levels higher that the values reported in human liver were exposed to mild oxidative stress with tert26 butylhydroperoxide. β-Carotene ( >2.6 nmol/mg protein) and astaxanthin (>1.8 nmol/mg protein) significantly inhibit lipid peroxidation, while β-cryptoxanthin and lutein did not. α-Tocopherol remarkably suppressed the lipid peroxidation with an IC50 value of 0.16 nmol/mg protein. Even at higher concentration. Neither α-tocopherol nor carotenoids except for lycopene showed prooxidant action. Further studies are necessary to assess the implications of the antioxidant behaviors found in the cultured cells on human health since antioxidant antivity of carotenoids in vitro were quite different from those found in liposome and homogenous solution.